An influence of interval hypoxic training on physical readiness indicators of trained mountaineers - Кийко, Андрій; Мулик, Вячеслав (Slobozhanskyi Herald of Science and Sport, 2017)
Andrii Kyiko & Viacheslav Mulyk Purpose: determine the influence of interval hypoxic training (IHT) on the indices of physical preparedness at the stage of precompetitive preparation for overcoming Mount Elbrus. Material & Methods: to determine the level of manifestation of physical qualities, the exercises recommended for the training of climbers and methods of mathematical statistics with the calculation of well-known indicators were used to establish the correlation dependence and the reliable difference between the group indices. Results: the conducted studies made it possible to establish that the use of the regime of discontinuous hypoxia 15–15 with breathing through the system into a closed space in the training process of the precompetitive period contribute to an increase in the indices of physical fitness of climbers. Conclusion: the results of the conducted studies indicate that the use of IHT in the 15–15 mode in the period before the ascent to the city of Elbrus allows to significantly increasing the indices of physical preparedness (mainly exercises with a delay in breathing) and the anaerobic and aerobic endurance of skilled climbers in the pre-competition stage.